Time‐evolving seismic tomography: The method and its application to the 1989 Loma Prieta and 2014 South Napa earthquake area, California - Ping Tong; Dinghui Yang; Dongzhuo Li; Qinya Liu (Geophysical Research Letters)
Abstract We propose a time‐evolving approach to conduct traveltime seismic tomography in the 1989 Mw 6.9 Loma Prieta earthquake and 2014 Mw 6.0 South Napa earthquake area, California. The recording period of the chosen seismic data between 1 January 1967 and the day before the 2014 South Napa earthquake is divided into two time windows, separated by the 1989 Loma Prieta earthquake. In each time window the subsurface velocity structure is iteratively updated. Starting from the final model of the first time window, the velocity model has been successively improved throughout iterations in the second time window, indicating that the traveltime data of later time windows have provided extra information to refine the subsurface images. Strong heterogeneities are observed in the final P wave velocity model. Both of the two large earthquakes occurred at transition zones in between high VP and low VP anomalies. In all, this study shows the effectiveness of the time‐evolving seismic tomography method.